Desempenho de bezerros mantidos em pastagem de aveia preta e azevém recebendo suplementação energética, advindos de pastagem de Tifton 85 - Pereira, Lucas Braido (2015)
The objective of this study was to evaluate the effect of supplementation levels in the final rearing stage, on pasture productivity aspects, body performance and animal behavior. Forty-four Bradford calves were used, prior to this study, the calves were weaned on Tifton 85 pasture, fed supplementation with an average age of nine months and average weight of 204.00; 211.00; 248.00 and 254,00kg in treatments S- 0,0; S- 0,5; S- 1,0 and S- 1,5 respectively. The treatments consisted of four levels of cracked-corn supplementation S- 0.0; S- 0.5; S- 1.0 and S- 1.5% of body weight (BW). The grazing method was continuous stocking with variable number of regulatory calves to keep the forage mass (FM) at the desired level of 1300 kg DM ha-1. For the variables related to the pasture, forage mass (FM), accumulation rate (AR) and herbage allowance (HA), no interaction (P>0.05) was found among the supplementation levels and the periods the pasture was used. MF, AR and HA presented interaction over the periods of use. However, when these variables were evaluated according to the treatments, except for herbage allowance, all others showed no significant difference. It was noted that the increase in supplementation level decreased forage supply linearly 2.876 kg MS (100 kg BW) -1. The stocking rate, body weight, body condition score and weight gain per area, showed interactions among periods and the treatments (P <0.05). The variable average daily gain weight showed no interaction (P> 0.05) among supplementation levels and periods of grazing. For the variables, rest time, rumination and time at feeding station, showed no interactions (P> 0.05) among treatments and periods. Rest and feeding station time, when analyzed according to supplementation levels showed a crescent linear regression, however, rumination time decreased linearly with the level of supplementation. When the variables were evaluated for the period of grazing, it was observed that time variables such as rest and rumination time, presented a quadratic behavior. Stocking rate presented interaction (P <0.05) among treatments and periods and increased as the supplementation level associated with the advancement of the physiological stage of the pasture increased. Displacement variables and bite size showed no significant difference (P> 0.05) according to the supplementation levels. Bite showed interaction (P <0.05) among treatments and periods. The black oats and ryegrass consortium, combined with supplementation provided the calves an increase in average daily weight gain, body condition, increases the stocking capacity of the pasture, reduces the time devoted to grazing, reduces rest time and increases rumination time.